Kinematics Analysis of 6-DoF Articulated Robot with Spherical Wrist. (2nd February 2021) - Asif, Seemal; Webb, Philip
Abstract : The aim of the paper is to study the kinematics of the manipulator. The articulated robot with a spherical wrist has been used for this purpose. The Comau NM45 Manipulator has been chosen for the kinematic model study. The manipulator contains six revolution joints. Pieper's approach has been employed to study the kinematics (inverse) of the robot manipulator. Using this approach, the inverse kinematic problem is divided into two small less complex problems. This reduces the time of analysing the manipulator kinematically. The forward and inverse kinematics has been performed, and mathematical solutions are detailed based on D-H (Denavit–Hartenberg) parameters. The kinematics solution has been verified by solving the manipulator's motion. It has been observed that the model is accurate as the motion trajectory was smoothly followed by the manipulator.